Characteristics of halide oxidation at graphite electrode for use in halide batteries. (June 2019) - Quintero Pulido, Diego F.; Kortenaar, Marnix V. ten; Hurink, Johann L.; Smit, Gerard J.M.
Abstract: The oxidation of halides, in particular bromide, has been studied in aqueous solutions on graphite electrodes by voltammetry, electrochemical impedance spectroscopy (EIS) and UV–Vis spectroscopy in light of its application in halide/halogen batteries used in microgrids. Voltammetry indicates fairly large differences in potentials and current density between different halide salts, concentrations, cation type and pH. Also, oxidation kinetics in 7MNaBr were much higher than in 7MZnBr2 solutions while no large differences were observed between these solutions at 2 M. This may be related to the effect that positive ions (Na + and Zn + ) may have an influence in halide oxidation kinetics at the large positive electrode potentials which indicated that local ionic potential effects affect the oxidation rate of the reaction. Moreover, EIS spectra seemed to go in line with this view, as there was a large resistance between ZnBr2 and NaBr in the electrolyte phase transfer element. This difference is possibly related to different polybromide formation rates (for the reaction Br − → Brx − + xe-). Additionally, results and literature shows that all data may be fitted by one equivalent circuit with the fitted circuit and Nyquist plots showing the complexity of the reaction by the presence of different resistors and capacitors.